Superimposing neuromuscular electrical stimulation onto voluntary contractions to improve muscle strength and mass: A systematic review - Borzuola, R.; Laudani, L.; Labanca, L.; Macaluso, A. (European Journal of Sport Science, 2022)
Training and rehabilitation programmes involving neuromuscular electrical stimulation superimposed onto voluntary contractions (NMES+) have gained popularity in the last decades. Yet, there is no clear consensus on the effectiveness of such intervention. The aim of this review was to evaluate the effect of chronic exposure to NMES+ on muscle strength and mass compared to conventional volitional training or passive electrical stimulation alone. Two authors conducted an electronic search to identify randomized controlled trials that investigated the effect of NMES+ training, involved healthy participants or orthopaedic patients, detailed a well-defined NMES training protocol, and provided outcomes related to muscle strength and/or mass. The authors extracted data on participants, intervention characteristics, muscle-related outcomes, and assessed the methodological quality of the studies. A total of twenty-four studies were included in the review. The majority of these reported an increase in muscle strength following NMES+ training compared to an equivalent voluntary or passive NMES training. The highest improvements were found when NMES was superimposed on sub-maximal exercises involving both concentric and eccentric contractions. Two studies reported an increase in muscle mass after NMES+, while two other studies exhibited no differences. This review indicated that chronic exposure to NMES+ determines muscle strength improvements greater or equal compared to volitional training alone. However, differences in the methodological characteristics of the stimulation and the type of exercise associated with NMES+ revealed significant discrepancies in the results. A deeper understanding of the neurophysiological adaptations to NMES+ is crucial to fully explain the muscle-related enhancement resulting from such intervention.